Comparative Analysis of Ultrasound and MRI in Detecting Endometriosis among Pakistani Women - Binish Zaidi, Sara Gill, Anum Farooq, Muhammad Imran Akhtar, Zeghum Hussain Zeghum, Sajida Majeed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Endometriosis is a persistent gynecological disease that greatly affects a woman’s quality of life and reproductive health. Diagnosis is increasingly done using such non-invasive imaging modalities as transvaginal ultrasound (TVUS) and magnetic resonance imaging (MRI). Nevertheless, data regarding their performance in detecting deep infiltrative lesions in Pakistani women, in particular, are scarce. Objective: To assess the diagnostic accuracy of TVUS compared to MRI in the detection of endometriosis in premenopausal Pakistani women using laparoscopic findings and histopathological confirmation as the reference standard. Methods: This is a prospective study of 12 months (January to December 2021) in 90 premenopausal women (aged 18 to 45 years) with clinical symptoms suggestive of endometriosis. TVUS and MRI evaluations were performed on all the participants before diagnostic laparoscopy. Images were interpreted by independent, experienced radiologists. Each imaging modality’s sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated and compared to laparoscopic and histopathological diagnosis. The diagnostic performance of DIE in a subset analysis was also performed. Results: Laparoscopy confirmed endometriosis in 70 patients (77.8%). In general, TVUS showed a sensitivity of 77.1%, specificity of 70.0%, PPV of 90.0%, and NPV of 46.7%. However, with significantly higher sensitivity (91.4%) and specificity (85.0%), PPV 95.5%, and NPV 73.9% (p < 0.05), MRI was found to be in contrast to the US. MRI has a sensitivity of 93.3% for deep infiltrating endometriosis as compared to 66.7% for TVUS. Moreover, the interobserver agreement for MRI (κ = 0.85) was greater than for TVUS (κ = 0.70). Conclusion: TVUS is still a cost-effective and accessible first-line diagnostic tool but MRI is superior for detecting deep infiltrative lesions. Therefore, the findings support a stepwise, tailored diagnostic approach in resource-constrained settings that incorporates MRI when TVUS findings are unspecific or deep disease is suspected to best guide patient management and surgical planning. Keywords: Endometriosis, Diagnostic Accuracy, Transvaginal Ultrasound, Magnetic Resonance Imaging, Deep Infiltrating Endometriosis, Pakistani Women, Laparoscopy